THE INFLUENCE OF SOCIAL MEDIA MARKETING ON BRAND EQUITY, BRAND TRUST AND BRAND LOYALTY ON TRAVELOKA INSTAGRAM - Tarisa, Tarisa; Giri , Refi Rifaldi Windya (JPIM (Jurnal Penelitian Ilmu Manajemen), 2024)
This research is entitled "The Effect of Social Media Marketing on Brand Equity, Brand Trust, and Brand Loyalty on Traveloka Instagram". The main focus is to understand the influence of social media marketing activities on brand trust, brand equity, and brand loyalty on Traveloka's Instagram platform. The background of this research is based on the estimation that the tourism industry in Indonesia is growing rapidly along with the widespread use of social media which affects marketing methods. The phenomenon in this study was explored using a questionnaire survey method using a Likert scale with the criteria of Instagram social media users and Traveloka applications in the DKI Jakarta area and SEM-PLS analysis. The purpose of this research is to identify the influence of social media marketing on Traveloka's brand trust, brand equity, and brand loyalty on Instagram. This is important given the growth of Indonesia's tourism sector and the important role of social media in the marketing strategy of online travel agents (OTAs). The results showed that social media marketing has a significant influence on brand equity, brand trust, and brand loyalty. In addition, the factor that needs to be considered is brand trust because it has the greatest influence than other variables, which indicates that consumers' trust in the brand affects their perception of value and their desire to remain loyal to the brand. The benefits of this research include theoretical contributions in the field of management, especially in the aspects of social media marketing, brand trust, brand equity, and brand loyalty, as well as practical benefits for academics and companies in planning marketing strategies and business development.